2017
DOI: 10.1016/j.bbmt.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Late Complications and Quality of Life after Reduced-Intensity Conditioning Allogeneic Stem Cell Transplantation

Abstract: Late complications (LC) and quality of life (QOL) were analyzed in 110 adult patients who underwent reduced-intensity conditioning (RIC) allogeneic stem cell transplantation (allo-SCT) and were alive for more than 2 years after allo-SCT. Overall survival of these patients was 93% (95% confidence interval [CI], 88% to 99%) and 81% (95% CI, 71% to 94%) at 5 and 10 years, respectively. The primary cause of death was a recurrence of primary malignancy. With a median follow-up of 4.6 years (range, 2 to 12.1), chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
(48 reference statements)
0
19
0
3
Order By: Relevance
“…We found aGVHD was an independent predictor for shorter OS and PFS, while cGVHD might prolong survival due to an accompanying GvM effect and can thus in a mild form be regarded as an advantageous feature. However, some studies have reported cGVHD was also related to chronic diarrhea, appetite loss and inferior QOL [ 90 , 96 , 97 ], and was the most important cause of TRM. Novel strategies for acute and chronic GVHD prevention need to be explored in the setting of allografting for MM.…”
Section: Discussionmentioning
confidence: 99%
“…We found aGVHD was an independent predictor for shorter OS and PFS, while cGVHD might prolong survival due to an accompanying GvM effect and can thus in a mild form be regarded as an advantageous feature. However, some studies have reported cGVHD was also related to chronic diarrhea, appetite loss and inferior QOL [ 90 , 96 , 97 ], and was the most important cause of TRM. Novel strategies for acute and chronic GVHD prevention need to be explored in the setting of allografting for MM.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that patients do not discuss cognitive impairment as they are not asked about it by staff as a side effect of treatment (Portora et al, 2010). Nurses should ask patients regularly about their memory and any challenges they may be experiencing to their concentration and recall, It is well known that neurocognitive deficits (referred to as "chemo brain"), have a huge impact on allogenic transplantation survivors' daily activities and a challenge for those who return to work (Inamoto, & Lee 2017;Clavert et al, 2017). Our understanding of neurocognitive effects following autologous transplantation is also of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is described in about 20-60% of patients. [119][120][121][122] Al-Hazzouri et al reported older age, hypertension, poor pre-transplant kidney function, diagnosis of multiple myeloma (MM), and use of CNIs for GvHD as risk factors for CKD. 123 Other authors reported that fludarabine administration was significantly associated with chronic renal impairment.…”
Section: Renal Dysfunctionmentioning
confidence: 99%